2023
DOI: 10.1186/s40100-023-00256-9
|View full text |Cite
|
Sign up to set email alerts
|

What sets cooperative farmers apart from non-cooperative farmers? A transaction cost economics analysis of coffee farmers in Mexico

Abstract: This study investigates what factors relate to the coffee farmer’s cooperative affiliation decision and whether this decision impacts the farmer’s cash holdings. First, we propose a cooperative affiliation model based on transaction cost economics theory. There is a lack of consensus in the literature on what factors explain the farmer’s cooperative affiliation decision in the coffee sector. Overall, we find that the more specialized coffee farmers are, the more likely they will become cooperative affiliates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…A study in China by [25] found that farmers who are in vertical integration have higher agricultural and total income than non-participants. Relatedly, a study by [26] in Mexico on what differentiate cooperative and non-cooperative smallholder farmers found that vertical integration specifically through cooperatives have statistical significant influence on farmers' offfarm income. Similarly, a study by [27] in Kosovo revealed that farmers engaged in vertically integrated market specifically cooperatives had higher income than non-members.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…A study in China by [25] found that farmers who are in vertical integration have higher agricultural and total income than non-participants. Relatedly, a study by [26] in Mexico on what differentiate cooperative and non-cooperative smallholder farmers found that vertical integration specifically through cooperatives have statistical significant influence on farmers' offfarm income. Similarly, a study by [27] in Kosovo revealed that farmers engaged in vertically integrated market specifically cooperatives had higher income than non-members.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%